2017
DOI: 10.5194/bg-2017-416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The competing impacts of climate change and nutrient reductions on dissolved oxygen in Chesapeake Bay

Abstract: Abstract. The Chesapeake Bay region is projected to experience changes in temperature, sea level, and 15 precipitation as a result of climate change. This research uses an estuarine-watershed hydrodynamicbiogeochemical modeling system along with projected changes in temperature, freshwater flow, and sea level rise for a 2050 scenario to explore the impact climate change may have on future Chesapeake Bay dissolved oxygen (DO) concentrations and the potential success of nutrient reductions in attaining mandated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 42 publications
3
58
1
1
Order By: Relevance
“…Despite the differences among the three RCM projections, the projected increases in hypoxia in this eutrophic estuary are similar. This increase of 10–30% in the hypoxic and anoxic volumes is larger than the increases obtained from the model runs that considered simplified changes from climate model projections (Irby et al, ; Wang et al, ), suggesting possible nonlinear synergistic effects among different climate change factors.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Despite the differences among the three RCM projections, the projected increases in hypoxia in this eutrophic estuary are similar. This increase of 10–30% in the hypoxic and anoxic volumes is larger than the increases obtained from the model runs that considered simplified changes from climate model projections (Irby et al, ; Wang et al, ), suggesting possible nonlinear synergistic effects among different climate change factors.…”
Section: Discussionmentioning
confidence: 63%
“…The simplified climate change numerical experiments by Wang et al () and Irby et al () showed that sea level rise amplifies the estuarine transport and leads to stronger import of higher‐O 2 coastal water to the hypoxic region in the mid‐Bay. The net effect of sea level rise on estuarine hypoxia ultimately depends on the competition between the stronger vertical stratification and stronger inflows and is the subject of an ongoing model intercomparison study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations